Reformulation of Fiqh Muamalah Theory in Relation to the Macroeconomic Policies of the Modern State - Abu Bakar; Muhammad Rifqi Ridho (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
This study aims to reformulate the theory of Jurisprudence of Muamalah so that it becomes relevant to the macroeconomic policies of the modern state, which have largely been dominated by conventional economic paradigms based on interest. Departing from the gap between the normative principles of muamalah such as the prohibition of riba (usury), distributive justice, transparency, and an orientation toward magasid al-shari'ah and modern fiscal and monetary instruments, this study examines the possibility of integrating Sharia values within the framework of public policy. The research employs a qualitative approach based on library research, using content analysis and critical synthesis of classical fiqh literature, Islamic economics, and contemporary macroeconomic studies. The findings indicate that Jurisprudence of Muamalah possesses conceptual potential as an ethical foundation for macroeconomic policy through the strengthening of redistributive instruments (such as zakat and waqf), the development of risk-sharing schemes within monetary policy, and the integration of social justice values into fiscal policy design. However, several methodological and structural challenges remain, particularly the dominance of the global interest-based financial system and the technocratic complexity of modern macroeconomic policymaking. The proposed reformulation positions Jurisprudence of Muamalah not merely as a set of private legal norms but as a normative–operational paradigm for building a just and sustainable economic system. This study contributes to the development of Sharia economic legal theory by presenting an integrative framework that connects the values of magasid al-shari'ah with the stability of modern macroeconomic systems.